Bank Consolidation, Efficiency, and Profitability in Italy - Weber, Anke. (Washington, D.C. : International Monetary Fund, 2017)
This paper examines the case for efficiency-driven banking sector consolidation in Italy, evaluates its potential effects on profitability, and discusses policy options to facilitate a consolidation process that is as effective as possible. A bottom-up analysis of 386 Italian banks suggests that while profitability is expected to improve as the economy gradually recovers, operational efficiency gains are nonetheless needed to restore large parts of the banking system to healthy profitability. Banking system consolidation can play a role in facilitating such efficiency gains, but its effectiveness is likely to be most as part of a comprehensive strategy that includes complementary reforms to clean up bank balance sheets. Cross-country experience indicates that efficiency gains are more likely to follow consolidations where careful viability analyses are conducted of the synergies and operational improvements that can be achieved.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet